2018
DOI: 10.3847/2041-8213/aabde9
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-periodic Pulsations in the Most Powerful Solar Flare of Cycle 24

Abstract: Quasi-periodic pulsations (QPP) are common in solar flares and are now regularly observed in stellar flares. We present the detection of two different types of QPP signals in the thermal emission light curves of the X9.3 class solar flare SOL2017-09-06T12:02, which is the most powerful flare of Cycle 24. The period of the shorter-period QPP drifts from about 12 to 25 seconds during the flare. The observed properties of this QPP are consistent with a sausage oscillation of a plasma loop in the flaring active re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 44 publications
4
36
0
1
Order By: Relevance
“…Usually, the damping time is determined from the best-fitting exponential decay function. But, it has been shown that in some cases a Gaussian decay is more appropriate [12,32]. Physical mechanisms responsible for the Gaussian damping of slow magnetoacoustic waves in the corona have not been identified yet, but are known in the case of coronal fast magnetoacoustic waves of the kink symmetry [44].…”
Section: Decaying Harmonic Qppmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, the damping time is determined from the best-fitting exponential decay function. But, it has been shown that in some cases a Gaussian decay is more appropriate [12,32]. Physical mechanisms responsible for the Gaussian damping of slow magnetoacoustic waves in the corona have not been identified yet, but are known in the case of coronal fast magnetoacoustic waves of the kink symmetry [44].…”
Section: Decaying Harmonic Qppmentioning
confidence: 99%
“…However the flare trend does have a significant impact on the shape of flare power spectra (e.g., [32]), and as such can make QPP signals much more difficult to detect [35]. Therefore there is a huge incentive to detrend flare light curves using an analytical model, in a way that does not risk introducing artificial signal that may be misinterpreted as QPP.…”
Section: The Trendmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence to support the theory that QPPs are a common feature of both solar and stellar flares (Kupriyanova et al 2010;Simões et al 2013;Inglis et al 2016;Pugh et al 2016Pugh et al , 2017. For example, they were recently observed in the largest solar flare of cycle 24 to date (Kolotkov et al 2018). This X9.3 class flare was estimated to have an energy of around 10 32 erg, and therefore bridges the energy gap observed between solar and stellar flares.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SOL2017‐09‐06 produced two coronal mass ejections, one near the peak time and the next 1 hr later (Goryaev et al, ). It was pointed out that the total emitted energy by the flare is about 10 (25) J, that is, in the lower limit of a super flare (Kolotkov et al, ). In this paper we report the observation of SOL2017‐09‐06 at the wavelengths of 10 μm (mid‐IR) and 0.7 and 1.4 mm (submillimeter).…”
Section: Introductionmentioning
confidence: 99%